Pengaruh Literasi Keuangan Dan Cognitive Style Terhadap Pengelolaan Keuangan Pada UMKM Dikota Langsa - Maya Sumarni; Tuti Meutia; Nasrul Kahfi Lubis (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This study aims to determine the effect of financial literacy and cognitive style on financial management in UMKM in Langsa City. The population of this study is all UMKM business actors in Langsa City, totaling 23,079 UMKM. The sampling technique uses the Stratified Sampling method where all UMKM actors are the sample. Data collection was carried out by distributing questionnaires to 100 respondents. The data obtained were then analyzed using SPSS (Statistical Package for the Social Sciences). The results of the research simultaneously show that financial variables and cognitive style together have a significant influence on UMKM financial management in Langsa City. While partially the financial literacy variable has no positive and significant effect on financial management of UMKM in Langsa City. And the cognitive style variable also has no positive and significant effect on financial management for UMKM in Langsa City. Finally, financial literacy and cognitive style together have a positive and significant effect on financial management for UMKM in Langsa City.